Impact of tourism IV the Gambia - TV Choice Production ([United Kingdom] : TV Choice Ltd., 2001)
Tourism has become the Gambia's major surce of income. But tourism here is a double-edged sword. Despite many visitors, little money ends up with local people. The holidays are organised by foreign tour operators and holiday makers spend their time in foreign owned hotels. This video tries to share how are Gambians trying to tackle these problems
Title from title screen
DVD format
Keywords: Tourism -- Gambia; Tourism